Influence of Interpersonal and Institutional Trust on the Participation Willingness of Farmers in E-Commerce Poverty Alleviation - Chen, Guoyi; Tan, Wei; Zhang, Shangmin; Yan, Bangquan (Frontiers in Psychology, 2021)
To explore the influence of interpersonal trust and institutional trust on the participation willingness of farmers in e-commerce poverty alleviation in China, a questionnaire survey of 320 farmers in Chongqing Ecological Tourism District was adopted for data collection, and a binary logistic model was used for data analysis. The results showed that (1) both interpersonal trust and institutional trust had a positive influence on the participation behavior of farmers in e-commerce poverty alleviation, and the priority ranking from high to low was: trust in government, trust in relatives, trust in neighbors, and trust in village cadres. (2) Institutional trust had a greater impact on the participation behavior of farmers than interpersonal trust, especially in the poverty-stricken areas where economic development was relatively backward. (3) Individual attributes, household attributes, and rural resource attributes had a significant positive impact on the participation intention of farmers. Among these, the role of rural e-business service platform was particularly important. The role of institutional trust at the village level still did not perform well in promoting the participation willingness of farmers. Based on empirical analysis, the suggestions for promoting the active cooperation of farmers and participating in the cooperation of e-business were put forward, such as enhancing the interpersonal network of farmers, improving the rural e-commerce information service platform, and strengthening the construction of the rural business environment.